Anything you don't know is invisible to your eyes: Educational interventions for serrated polyps can increase their detection. Issue 1 (14th July 2021) - Imai, Kenichiro
Abstract : This Editorial refers to the article by J. Lee et al., p 180‐190 of this issue.